Disabled veterans in history - Gerber, David A., 1944- (Ann Arbor : University of Michigan Press, 2012)
"Disabled Veterans in History explores the long-neglected history of those who have sustained lasting injuries or chronic illnesses while serving in uniform. The contributors to this volume cover an impressive range of countries in Europe and North America as well as a wide sweep of chronology from the Ancient World to the present. The essays address the emergence of "veteran" as a political category with unique privileges and entitlements and of disabled veterans as a special project--and indeed one of the original projects--of the modern welfare state. The introductory essay, "Finding Disabled Veterans in History," offers perhaps the first attempt at synthesizing knowledge about disabled veterans in Western societies. The other essays examine the representation of disabled veterans from Sophocles' Philoctetes to American feature films; the relations of disabled veterans to the state and society in such public policy issues as pensions, medical care, physical rehabilitation, and job retraining; and the disabled veteran's agency and experience in reentering the peacetime world. Other topics include the place of disabled veterans in societies defeated in war; the fate of disabled veterans in societies experiencing frequent changes of political regimes; the emergence of pensions and vocational rehabilitation for disabled veterans; and the abiding problem of alcohol abuse among disabled veterans. The contributors come from a variety of disciplines, including history, physical rehabilitation, Slavic studies, sociology, communication and media, and museum studies. The book will be of interest especially to researchers in the fields of war and society, the welfare state, and disability studies, as well as those in the medical, rehabilitation, and counseling fields. David A. Gerber is Professor of History, State University at Buffalo."--Project Muse.
Introduction : finding disabled veterans in history / David A. Gerber -- Representation. Philoctetes in historical context / Martha Edwards -- Heroes and misfits : the troubled social reintegration of disabled veterans in The best years of our lives / David A. Gerber -- Bitterness, rage, and redemption : Hollywood constructs the disabled Vietnam veteran / Martin F. Norden -- Public policy. Disabled veterans and the state in early modern England / Geoffrey L. Hudson -- "A sacred debt" : veterans and the state in revolutionary and Napoleonic France / Isser Woloch -- From individual trauma to national policy : tracking the uses of Civil War veteran medical records / Robert I. Goler and Michael G. Rhode -- Work-therapy and the disabled British soldier in Great Britain in the First World War : the cased of Shepherd's Bush Military Hospital, London / Jeffrey S. Reznick -- "Empty sleeves and wooden pegs" : disabled Confederate veterans in image and reality / R.B. Rosenburg -- Fifty years of pain : the history of Austrian disabled veterans after 1945 / Gregory Weeks -- Disabled Russian War veterans : surviving the collapse of the Soviet Union / Ethel Dunn -- Living with a disability : adjustments and maladjustments. Nomads in blue : disabled veterans and alcohol at the national home / James Marten -- Will to work : disabled veterans in Britain and Germany after the First World War / Deborah Cohen -- Lieutenant John Counsell and the development of medical rehabilitation and disability policy in Canada / Mary Tremblay -- Post-modern American heroism : anti-war war heroes, survivor heroes, and the eclipse of traditional warrior values / David A. Gerber -- Afterword : a challenge to historians / Jonathan Shay.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: History; Disabled veterans; SOCIAL SCIENCE -- People with Disabilities; Disabled veterans; History; SOCIAL SCIENCE / People with Disabilities; Electronic books